Interseasonal Difference in MJO Propagation during the Extended Boreal Winter: Observations and Climate Model Simulations - Back, Seung-Yoon; Kim, Daehyun; Son, Seok-woo; Kang, Daehyun (American Meteorological Society, 2025)
This study investigates climatological interseasonal changes in the Madden–Julian oscillation (MJO)’s propagation diversity using observational data and climate model simulations, with a particular focus on the role of the mean state. In observations, the ratio of the relative frequency of the fast-propagating MJO to that of the slow-propagating MJO shows notable changes from winter to early spring, with a significantly higher ratio during March–April (MA) than during November–February (NDJF). Column-integrated moisture budget analysis reveals that moisture recharge and discharge around the Maritime Continent, which drive the MJO’s eastward propagation, are stronger in MA, with zonally broader and stronger positive moisture tendency to the east of enhanced convection. Further analysis shows that stronger zonal moisture advection is responsible for the enhanced moistening in MA, which differs from NDJF, largely due to the steeper background zonal moisture gradient. The interseasonal difference in the moisture gradient between MA and NDJF appears to be associated with the Australian monsoon. Among the global climate models analyzed, those that better capture the interseasonal changes in zonal moisture gradients around the Maritime Continent tend to also better simulate the interseasonal difference between MA and NDJF in the relative frequency of slow- and fast-propagating MJOs. The model bias in the mean state moisture gradient seems to be caused by a delayed phase transition of the Australian monsoon. Our results suggest that reducing these biases can enhance model performance in simulating the interseasonal changes in the MJO propagation characteristics.